Estetika, Seren taun Antara Seni, Ritual, Dan Kehidupan - Subiantoro, Ign. Herry (PANGGUNG, 2016)
ÃÂ ABSTRACTÃÂ Seren taun presents a ceremony system which has aspects of ideas, aspect of language, aspect of behaviour and aspect of equipments. These aspects is related to one another and understood as a sacred communication. Three life principles as the conditions to achieve as the perfection of life and The Truth of death is ritualized on the Pwahaci as the birth symbol, the priciple of maturity and the image of per- fection (death).Under Djati Kusumah leaderships, Seren taun was developing physically as well as the content of appreciation presentation of the ADS spiritual, be able to be accepted by the community. SerenTaun is seen as guidance of aesthetical beauty in the trilogy of verum, bonum,ÃÂ  and pulchrum. Beautiful ways to present aesthetic of Seren taun which is anticipate the nature beauty and art as the safety signs, there are shown by the guidance of the harmonization between human beings and God, the nature and other human beings. The art and ritual performance are kinds and true gives the universal as the harmoniza- tion and balance of humansÃ¢â¬â¢lives physically and mentally.ÃÂ Keywords: Seren taun, ritual performance, aesthetic of beauty, and balancing of humansÃ¢â¬â¢livesÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Seren taun merupakan presentasi estetik masyarakat agraris untuk mendatangkan berkah dari leluhur. Sistem upacara meliputi aspek gagasan, kebahasaan, prilaku, dan peralatan dalam seren taun dimaknai sebagai komunikasi sakral. Tiga prinsip kehidupan sebagai syarat menca- pai kesempurnaan hidup diritualisasikan pada Dewi Pwahaci untuk mengungkapkan tentang prinsip kelahiran, kedewasaan, dan gambaran prinsip kesempurnaan (kematian).Di tangan Kekarismatikan pemimpin tradisional Pangeran Djati Kusumah, Seren taun berkembang baik secara bentuk maupun isi, sebagai ÃÂ presentasi penghayatan ajaran spiritual ADS, agar mudah diterima oleh semua orang. Pemahaman itu menunjukan Seren taun sebagai tuntunan nilai-nilai keindahan, yang syarat dengan trilogi antara verum (kebenaran) bonum (ke- baikan), dan pulchrum (keindahan). Cara-cara indah dari presentasi estetik Seren taun merupa- kan keindahan alam dan seni sebagai tutuntunan-keharmonisan manusia dengan Tuhan, alam semesta, dan sesamanya. Pertunjukan seni dan ritual itu, memberikan manfaat secara universal sebagai penyelaras atau balancing kehidupan manusia secara lahir maupun batin.ÃÂ Kata kunci: Seren taun, estetika, pertunjukan ritualÃÂ